Hubungan Asupan Gizi dengan Produksi Asi Ibu Menyusui Bayi 0-6 Bulan Puskesmas Langa Kabupaten Ngada - Erlinda Permatasari; Echa Kristina Ule (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
This study aimed to determine the relationship between nutritional intake and breast milk production in mothers who breastfeed babies aged 0-6 months at Langa Health Center, Ngada Regency. This study was an analytic survey with a cross sectional design. The sample of this study amounted to 75 respondents consisting of mothers who breastfed babies aged 0-6 months at Langa Health Center, Ngada Regency. The sampling technique used probability sampling technique with simple random sampling technique. The results of the multiple regression equation showed that the variables X3 (fat), X4 (carbohydrate), X5 (vitamin A), X11 (zinc), X12 (vitamin D), X13 (vitamin B12), and X14 (sulfur) had positive values, which means that there is a unidirectional influence between the independent variable (nutritional intake) and the dependent variable (breast milk production). The results of statistical calculations obtained the correlation coefficient is r = 0.429, meaning that it has a moderate relationship with the coefficient of determination / square is 0.184 or equal to 18.4%. And from the calculation results it is known that the variable X3 (fat) obtained a t-count of (2.226) ˃ t-table (1.670) and obtained a significant value of 0.030 <0.05, it can be concluded that fat affects milk production, so the hypothesis is accepted. From the results of the study, it is expected that breastfeeding mothers and the Langa Health Center share information about sources of nutritional intake, so that the increase in breast milk production for breastfeeding mothers can be guaranteed.